Tax amnesty from the perspective of tax official - Nur Sayidah; Aminullah Assagaf (Cogent Business & Management, 2019)
This article aims to analyze the views on tax amnesty from various parties, namely state officials, tax officials, taxpayers, and tax consultants. Their views are explored through qualitative research methods. The selected informants included four tax officials, two taxpayers, tax consultants, and state officials. State officials who are the source of the data are the President, Ministry of Finance, Secretary-General of the Ministry of Finance, legislative members, and Finance Minister Staff on tax compliance. Data collection techniques are carried out by unstructured interviews, sending open questions to informants, listening to and recording television programs that related to tax amnesty, attend and record seminars on tax amnesty and download transcripts of speeches and exclusive interviews of state officials published by the Ministry of Finance's official website. The government regulates the implementation of the tax amnesty in Indonesia through Tax Law No. 11 of 2016. Taxpayers who repatriate and declare their assets receive amnesty with the consequence of paying the ransom. The analysis shows that the purpose of tax amnesty to repatriate funds to the country can be realized. The application of tax amnesty can increase tax revenue in the budget state. APBN In the future, strict legal processes need to be implemented for citizens who save money in other countries if a complete information system is available. For honest taxpayers, tax amnesty is a good policy from the government to forgive past tax mistake with a greater purpose. The government can build infrastructure to drive the economy.
Keywords: 650; tax amnesty; tax revenue; tax official; the taxpayer